PERAN PEMERINTAH DAERAH DALAM PENERTIBAN JAMAAH AHMADIYAH DI DESA SUNGAI MERANTI DARUSSALAM KECAMATAN PUJUD KABUPATEN ROKAN HILIR TAHUN 2008-2012 - Juliana "; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine the role of Local Government in to curb the Ahmadiyah community in Sungai Meranti Darussalam Pujud Rokan Hilir Year 2008-2012. Knowing the limiting factors regulating Local Government against the Ahmadiyah community in Sungai Meranti Darussalam Pujud Rokan Hilir. According to Paul Conn in Ramlan Surbakti book, conflict is basically divided into conflict win-lose (zero-sum coflict) and a win-win conflict (non-zero-sum conflict). Conflict winning or losing is antagonistic conflict situations it is not possible to achieve a compromise between the parties involved in the conflict. Win-win conflict is a conflict situation in which the parties involved in the conflict is still possible to compromise and work together so that all parties will get part of the conflict. The method used in this research is qualitative methods of data that is manifested in the form of a portrait explanation state forms, processes and specific pristiwah. Data collection techniques used were Interviews, Observation, Documentation.From the data obtained findings that the presence of the Ahmadiyya Community in Sungai Meranti Darussalam then there was a conflict between the village of Sungai Meranti Darussalam By Ahmadiyya Chairman of the Indonesian Ulema Council in Rokan Hilir eager to join the Local Government to dismiss Ahmadiyya of Rokan Hilir particular in Sungai Meranti Darussalam. The regional government said one of the fathers Subdistrict: not I do not want to participate dismiss Ahmadiyya but it is very difficult when we asked questions about Islam, because they are memorized the Qur'an than in our Islamic religion. That shortage of Islam on his own knowledge of His religion and do not want to deepen the Qur'an Islam only as a symbol of national identity card (KTP).Keywords: Role of Local Government, Ahmadiyya, Assembly Ulamah Indonesia